The deer play in Wuqinxi and four-point hand−knee kneeling positions for training core muscle function and spinal mobility - Chang, Xiao-Qian; Chen, Xin-Peng; Shen, Yi-Xin; Wang, Kuan; Huang, Shang-Jun; Qi, Yan; Niu, Wen-Xin (Frontiers in Bioengineering and Biotechnology, 2022)
In a traditional Chinese exercise Wuqinxi, the deer play is performed in a hand-foot kneeling position (HFK), which is remarkably similar to the conventional core stabilization exercise, four-point hand-knee kneeling position (HKK). However, the differences of these two positions is poorly understood. This study was to investigate muscle activation patterns and spinal kinematics during specific core stabilization training to provide evidence for selecting specific exercises. Nineteen healthy adults were recruited to perform HFK and HKK. The rotation angle of C7-T4 vertebra, and the surface EMG signals of abdominal and lumbar muscles on both sides were collected. The paired t-test showed that the vertebrae rotation angles were significantly higher during HKK than HFK, and the intra-group differences mainly occurred at the level of the thoracic vertebra. The muscle activation of both sides of rectus abdominis and external oblique in the HFK were significantly higher than HKK when the upper limb was lifted (p<0.05). While the activation of the ipsilateral lumbar multifidus and erector spinae muscles were significantly higher during HKK position than during HFK when the lower limb was lifted (p<0.05). The HFK provided more training for strengthening abdominal muscles, while the HKK could be recommended for strengthening lumbar muscles and increasing spine mobility. These findings can be used to help physiotherapists, and fitness coach and others select specific core exercises and develop individualizes training programs.